Die ondersteuning van okkulte-gerehabiliteerdes: 'n pastoraal-teologiese model vir die toerusting van fasiliteerders - B. M. J. de Beer; J. A. van den Berg (Acta Theologica)
The involvement of the occult-possessed in paganism and Satanism, in particular, seems to be extremely destructive. This destructiveness permeates every aspect of the possessed person’s life. After evangelisation, deliverance, and the start of therapy for underlying psychological problems, the occult-possessed person’s status changes to that of an occult-rehabilitee. The occult-rehabilitee’s social interaction and relationshipsmust be rebuilt and restored. This orientation and reinstatement in the community is an extremely complex and time-consuming activity. Specialised persons such as physicians, therapists and others are involved in the psychological and physical treatment aspects of the occult-rehabilitee. However, these specialists cannot assist the occultrehabilitee during the entire programme of orientation and reinstatement on account of their workload. A facilitator. i.e. an informal helper, is therefore the ideal person to assist the occult-rehabilitee. Due to the complex nature of this task, a facilitator therefore requires specific equipment and training. When assisting the occult-possessed and the occult-rehabilitee, a facilitator is exposed to a person who has been directly involved with the occult. The study is based on a pastoral-theological epistemology. An eclectic model is also preferred when handling the occult-possessed and in the subsequent facilitating process.